The Differences in Interpersonal Competences of Junior and Medior Sisters of the Congregation of the Sisters of Charity of St. Charles Borromeus, in the Indonesian Province - Fransiska Romana Ayu Triani (Journal of Counseling and Humanistic Studies, 2026)
This research uses a comparative quantitative method with the aim to: 1) To find out whether there is a difference in the interpersonal competence of junior and medior sisters in the Congregation of the Sisters of Charity of St Carolus Borromeus 2) To measure how high the level of interpersonal competence of Junior Sisters is 3) To measure how high the level of interpersonal competence of Medior Sisters is 4) To identify items in the interpersonal competence scale that are detected as not optimal or low that can be proposed as coaching topics.The subjects of this study were sisters of the Congregation of the Sisters of Charity of St Carolus Borromeus Province of Indonesia, involving 149 respondents consisting of 70 Junior Sisters and 79 Medior Sisters. This study used an interpersonal competence scale consisting of 54 used items with 5 aspects, namely: 1) Empathy; 2) Communication skills; 3) Social integration; 4) Relationship satisfaction; 5) Relationship conflict. This scale has good reliability with an Alpha Cronbach reliability index of 0.935. Assumption testing found the data to be non-normally distributed and inhomogeneous. Because the assumption test was not met, the Mann whitney non-parametric t-test was used. The results of this study are: 1) Interpersonal Competence of Medior Sisters (mean: 188.380) is higher than Junior Sisters (mean: 179.243) with p 0.001. 2) Interpersonal competence of junior sisters tends to be very high (59%); 3) Competence of mid-level sisters tends to be very high (67%); 4) There are 4 items (30,32,36,53) with the lowest scores that fall into the medium category that are given proposed coaching topics.